Pengembangan Media Pembelajaran E-Book Fisika Menggunakan 3d Pageflip Profesional Terintegrasi Ayat Al-Qur’an Siswa Kelas XI MAN 2 Padang - Sari, Milya (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This development aims to produce and develop e-book physics learning media using 3D Pageflip Professional on Learning that meets valid, practical and effective eligibility criteria. This research is a type of research development or Research and Development (R & D) with procedural model adapting 4-D models that define, design, develop and disseminate. Data obtained from validated questionnaires were given to 2 media experts, 2 material experts, 1 linguist, 1 commentator, 2 educators and 70 students. Based on the average result of the validation test by 6 validators the average value of 90.3%, very practical for educators with an average grade of 92.8% and is classified as very practical to use learners with an average value of 85%, and Very effective with the average value of 80.62%. Therefore, it can be concluded that the e-book physics learning media using 3D Pageflip Professional is feasible to be used as a medium of learning that meets the criteria of validity, practicality, and effectiveness and can increase learning interest of learners .